A second great transformation in Europe: The rise and imminent fall of the technocrats. Issue 4 (March 2015) - Stråth, Bo
<x xml:space="preserve">Abstract</x> Bo Stråth traces the rise of the technocracy – the 'political abandonment of politics' – and its spread from the EU to its member states. If Europe's institutions are to survive the crisis of legitimacy, he argues, the 'market Europe' consensus must end and a 'social Europe' must emerge.